Mga Modulates Bmpr1a Activity by Antagonizing Bs69 in Zebrafish - Sun, Xiaoyun; Chen, Ji; Zhang, Yanyong; Munisha, Mumingjiang; Dougan, Scott; Sun, Yuhua (Frontiers in Cell and Developmental Biology, 2018)
MGA (MAX giant associated protein) is a dual transcriptional factor containing both T-box and bHLHzip DNA binding domains. In vitro studies have shown that MGA functions as a transcriptional repressor or activator to regulate transcription of promotors containing either E-box or T-box binding sites. BS69 (ZMYND11) is a multidomain-containing (i.e., PHD, BROMO, PWWP, and MYND) protein. BS69 has been shown to selectively recognizes histone variant H3.3 lysine 36 trimethylation (H3.3K36me3), modulates RNA Polymerase II elongation, and functions as RNA splicing regulator. Mutations in MGA or BS69 have been linked to multiple cancers or neural developmental disorders. Here, by TALEN and CRISPR/Cas9-mediated loss of gene function assays, we show that zebrafish Mga and Bs69 are required to maintain proper Bmp signaling during early embryogenesis. We found that Mga protein localized in the cytoplasm modulates Bmpr1a activity by physical association with Zmynd11/Bs69. The Mynd domain of Bs69 specifically binds the kinase domain of Bmpr1a and interferes with its phosphorylation and activation of Smad1/5/8. Mga acts to antagonize Bs69 and facilitate the Bmp signaling pathway by disrupting the Bs69-Bmpr1a association. Functionally, Bmp signaling under control of Mga and Bs69 is required for properly specifying the ventral tailfin cell fate.